2021
DOI: 10.1177/0032258x211024690
|View full text |Cite
|
Sign up to set email alerts
|

Proof of concept and feasibility of the app-based ‘#SWPMoveMore Challenge’: Impacts on physical activity and well-being in a police population

Abstract: An app-based physical activity intervention (#SWPMoveMore Challenge) was completed by 239 workers from one UK police force using a quasi-experimental design. Impacts were assessed against minutes of movement, individual difference and work-related stress variables using quantitative and qualitative approaches. The concept was feasible and translatable to a UK police population and the intervention significantly benefited direct measures of physical activity and perceptions of vitality, job stress, job satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In other words, while there is a considerable amount of literature supporting “why” LEO’s should engage in physical activity, few studies have focused on “how” to engage LEO’s in physical activity. A recent study from Oliver et al (2022) suggests that an app-based physical activity intervention can increase short-term physical activity participation in LEO’s. Nevertheless, the long-term effects of such intervention are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, while there is a considerable amount of literature supporting “why” LEO’s should engage in physical activity, few studies have focused on “how” to engage LEO’s in physical activity. A recent study from Oliver et al (2022) suggests that an app-based physical activity intervention can increase short-term physical activity participation in LEO’s. Nevertheless, the long-term effects of such intervention are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…While participation in physical activity courses seems to have considerable benefits for the health of LEOs, promoting LTPA participation remains a challenge for law enforcement agencies. Oliver et al 55 have shown that the implementation of an app-based physical activity intervention in police organizations can lead to short-term increases in physical activity participation and decreases in job-related stress. In a recent qualitative study, LEOs identified their work schedule as the main barrier to physical activity participation 56 .…”
Section: Discussionmentioning
confidence: 99%